A need for investigating organizational climate and its impact on the performance - Lafta, Ahmed Hamden; Man, Norsida; Mohammed Salih, Jasim; Abu Samah, Bahaman; Mohd Nawi, Nolila; Raja Yusof, Raja Nerina (IISTE, 2016)
The role of agricultural extension in the development of agriculture throughout the world is very significant. It has remained one of the prime movers in the development of agriculture and invariably in the rural development. This paper reviewed some literature in organizational climate and its impact on the performance of agricultural extension workers in Iraq. The paper introduces some basic concepts underlying the meaning of agricultural extension, organizational climate and performance. The motivations and attentions are given to organizational climate to show through the relationship between the organizational climate and the other organizational changes, especially in the area of interaction between the individual and the regulatory environment which is determined by two basic axes. First axis is the individual’s characteristics associated to a large extent to his knowledge system and his educational and cultural experiences. The second axis represents the internal work environment which describes the distinctive features of the organization. This paper distinguishes some characteristics which are organizational structure, communication system, and the nature of the work, leadership style, decision-making styles, colleagues of work, and the nature and physical of working environment.